Leaching process in the preparation of Raney cobalt catalyst - Abacioglu, Kurtulus; Salt, Yavuz (SPRINGER, 2010)
Raney metal type Co-Al alloy consisting of 36 wt% Co and 64 wt% Al was prepared by melting cobalt and aluminum metals in argon atmosphere, and then by solidification the resultant intermetallic compound. Raney Co catalyst was prepared by leaching out aluminum from Co-Al alloy with sodium hydroxide solution. The effects of reaction temperature (10, 25 and 40 A degrees C), concentration of sodium hydroxide (2, 4 and 6 M), solid to liquid ratio (2, 3 and 4 g/L) on the leaching were investigated by following the increase of the amount of aluminum in the reaction mixture. The structural properties of the alloy and the catalyst were examined by XRF, SEM, XRD and BET analysis. The kinetic model best fitting the experimental results among various models was determined.
Keywords: Raney cobalt; Alloy; Leaching; Catalyst; SILVER CATALYST; KINETICS; HYDROGENATION; DECOMPOSITION; METHANE; PHASE; CO; Chemistry